2018
DOI: 10.30682/nm1804e
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Preferences for Enhancing Sustainability in Arable Lands: Evidence From a Choice Experiment in Sicily

Abstract: We used discrete-choice experiments (DCE) to elicit farmers' preferences among alternative agrienvironmental schemes (AES) designed to reduce soil risk of erosion, maintain soil fertility, enhance countryside landscape, and preserve agrobiodiversity in arable lands of Sicily (Italy). Using appropriate models, we also investigated farmers' preference heterogeneity and spatial correlation. The results demonstrated a general positive and highly heterogeneous attitude in farmers toward the adoption of environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…Respondents are asked to choose their preferred alternative based on a set of hypothetical scenarios known as the choice set in this method [46]. Many studies have used the CE approach to investigate contract attributes, such as coffee farmers' preferences for coffee certification [10], contract attribute design [33], farmers' preferences for increasing sustainability in arable land [6] and sustainable farm management contracts [19]. Individuals are expected to choose one option that maximizes the utility or satisfaction of each alternative package presented to them when CE is implemented.…”
Section: Choice Experiments Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents are asked to choose their preferred alternative based on a set of hypothetical scenarios known as the choice set in this method [46]. Many studies have used the CE approach to investigate contract attributes, such as coffee farmers' preferences for coffee certification [10], contract attribute design [33], farmers' preferences for increasing sustainability in arable land [6] and sustainable farm management contracts [19]. Individuals are expected to choose one option that maximizes the utility or satisfaction of each alternative package presented to them when CE is implemented.…”
Section: Choice Experiments Approachmentioning
confidence: 99%
“…It's crucial to recognize and comprehend the taste or location-specific preferences of farmers. Understanding and knowledge about preferences seeks to make certification scheme implementation more effective [6] has a higher or adoptable degree of acceptance [5,7], and can be accepted by farmers [8,9]. It is suggested that the design of partnership and certification programs involve the local community in the development of partnership attributes and certification requirements [10].…”
Section: Introductionmentioning
confidence: 99%
“…We observed 15 studies used this attribute to test its impacts on contract design, and 8 out of those showed that farmers prefer to enroll shorter areas into the contracts, while 6 showed no role of significance. Studies have indicated this as a conflict between agricultural intensification and conservation (De Salvo et al, 2018;Espinosa-Goded et al, 2010;Villamayor-Tomas et al, 2019;Villanueva et al, 2015a). Farmers also have a high reluctance and strong disutility for larger conservation areas or larger forest sizes.…”
Section: Area Enrolled In Contract (%)mentioning
confidence: 99%
“…The attribute is also similar to 'communal participation', with the only difference being that this tests the farmer's preferences to his immediate neighbor's preferences, whereas the latter is on the level of the whole community. De Salvo et al (2018) suggested that neighbor-effect can improve acceptability of AESs and achieve cost-effectiveness of contracts, and hence farmers' preferences for 'local context' should be considered by policymakers.…”
Section: Prescription Attributesmentioning
confidence: 99%
“…It is still unclear, however, whether the trust in long-term buyers itself, rather than a contract, may be an avenue to reach these farmers and whether that will suffice to induce a change in practices, considering that some farmers may also be principally opposed to certain (agro-ecological) practices (Jaeck & Lifran, 2014). Thus, to maximise uptake of sustainable practices, heterogenous preferences for both contracts and practices need to be taken into account (Mack et al, 2020;Salvo et al, 2018). This indicates that there are limitations to what a voluntary private sector approach can achieve in terms of improving the uptake of more SI practices.…”
Section: Discussionmentioning
confidence: 99%